INFORMATION MANAGEMENT MODEL TOWARDS CONNECTED GOVERNMENT IN YOGYAKARTA SPECIAL PROVINCE - Agung Harimurti; Achmad Djunaedi; Wahyudi Kumorotomo (Puslitbang Literasi dan Profesi SDM Komunikasi dan Informatika, 2015)
The research is entitled “information management model towards connected government in Yogyakarta Special Province (Pemda DIY)”. The aim of the research is recommend the information model towards connected government concept in Pemda DIY. The study used a qualitative approach and soft system methogology (SSM). While data collection techniques used were depth interviews, observation, and foccus group discussion. The results indicate that information management in Pemda DIY govern sectoral each element and independently. The result contribution show that importance the GCIO and special unit for information manajement in public sector.Keywords: Information manajement, Modelling, Soft System Methodology, Connected Governmet